Gypsum amendment to rice paddy soil stimulated bacteria involved in sulfur cycling but largely preserved the phylogenetic composition of the total bacterial community. Issue 3 (11th May 2016) - Wörner, Susanne; Zecchin, Sarah; Dan, Jianguo; Todorova, Nadezhda Hristova; Loy, Alexander; Conrad, Ralf; Pester, Michael
Summary: Rice paddies are indispensable for human food supply but emit large amounts of the greenhouse gas methane. Sulfur cycling occurs at high rates in these water‐submerged soils and controls methane production, an effect that is increased by sulfate‐containing fertilizers or soil amendments. We grew rice plants until their late vegetative phase with and without gypsum (CaSO4 ·2H2 O) amendment and identified responsive bacteria by 16S rRNA gene amplicon sequencing. Gypsum amendment decreased methane emissions by up to 99% but had no major impact on the general phylogenetic composition of the bacterial community. It rather selectively stimulated or repressed a small number of 129 and 27 species‐level operational taxonomic units (OTUs) (out of 1883–2287 observed) in the rhizosphere and bulk soil, respectively. Gypsum‐stimulated OTUs were affiliated with several potential sulfate‐reducing ( Syntrophobacter, Desulfovibrio, unclassified Desulfobulbaceae, unclassified Desulfobacteraceae ) and sulfur‐oxidizing taxa ( Thiobacillus, unclassified Rhodocyclaceae ), while gypsum‐repressed OTUs were dominated by aerobic methanotrophs ( Methylococcaceae ). Abundance correlation networks suggested that two abundant (>1%) OTUs ( Desulfobulbaceae, Rhodocyclaceae ) were central to the reductive and oxidative parts of the sulfur cycle.